Fabrication of porous ceramic scaffolds via polymeric sponge method using sol-gel derived strontium doped hydroxyapatite - Sopyan, I.; Mardziah, C.M.; Ramesh, S. (2012)
Recently, development of porous calcium phosphates ceramics has raised considerable interest. A porous structure promotes cell attachment, proliferation and provides pathways for biofluids. Therefore, a high porosity with interconnected pore structure generally favors tissue regeneration. In this work, replication of 0, 2, 5, 10 and 15 SrHA (strontium-doped hydroxyapatite) porous scaffolds via polymeric sponge method has been employed using the sol-gel derived SrHA powders. To prepare the porous samples, the synthesized Sri-IA powders were mixed with distilled water and dispersing agent followed by drying in the ambient air and specific sintering process. Morphological evaluation by FESEM measurement revealed that the SrHA scaffolds were characterized by macro-micro interconnected porosity, which replicates the morphology of the cancellous bone. Compression test on the porous scaffolds revealed that doping 10 mol of strontium in HA has increased the compressive strength by a factor of two compared to the undoped HA with 1.81+/-0.26 MPa at 41 porosity.